2009
DOI: 10.1177/1756283x08100666
|View full text |Cite
|
Sign up to set email alerts
|

sPECAM-1 and sVCAM-1: role in pathogenesis and diagnosis of chronic hepatitis C and association with response to antiviral therapy

Abstract: Hepatitis C virus (HCV) infection results in upregulation of sPECAM-1 and sVCAM-1. sPECAM-1 levels are related to necroinflammatory activity and may also identify patients with advanced fibrosis. The sPECAM-1 value was decreased by therapy but its measurement cannot predict therapy outcome and confirm HCV persistence. sPECAM-1 may influence VCAM-1 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Visfatin may also induce VCAM-1 and ICAM-1 synthesis directly in endothelial cells and leukocytes by activation of nuclear factor (NF)-κB (25,51). Both these adhesion molecules are significantly increased in CHC (47,52), and serum ICAM-1 concentration is associated with the inflammatory activity grade (47). These findings suggest that visfatin directly, together with TNFα, or through induction of TNFα, may enhance production of adhesion molecules and therefore may have a pivotal role in the regulation of the necro-inflammatory process in the liver and facilitates migration of immune cells to the site of inflammation.…”
Section: Visfatin and Necro-inflammatory Activity In Chronic Hepatitismentioning
confidence: 99%
“…Visfatin may also induce VCAM-1 and ICAM-1 synthesis directly in endothelial cells and leukocytes by activation of nuclear factor (NF)-κB (25,51). Both these adhesion molecules are significantly increased in CHC (47,52), and serum ICAM-1 concentration is associated with the inflammatory activity grade (47). These findings suggest that visfatin directly, together with TNFα, or through induction of TNFα, may enhance production of adhesion molecules and therefore may have a pivotal role in the regulation of the necro-inflammatory process in the liver and facilitates migration of immune cells to the site of inflammation.…”
Section: Visfatin and Necro-inflammatory Activity In Chronic Hepatitismentioning
confidence: 99%
“…Other authors have indicated that patients with HCV infection who were treated with interferon had decreased circulating levels of ICAM-I if they attained an SVR [21,22]. In contrast, a 2009 study assessed the levels of this marker in patients with HCV before and after antiviral treatment and revealed that sVCAM-I levels were higher in patients with more advanced stages of fibrosis, but the levels did not predict treatment response [15]. Subsequently, another study [23] including 134 patients with chronic liver disease concluded that the VCAM level is related to a Child-PughC.…”
Section: Discussionmentioning
confidence: 99%
“…HCV infection leads to inflammatory processes of different grades that involve the activation of adhesion molecules and cytokines that facilitate the recruitment of leukocytes to areas of inflammation [15]. Liver fibrosis follows hepatic inflammation as a result of hepatocyte injury [16].…”
Section: Discussionmentioning
confidence: 99%
“…sICAM-1, sVCAM-1, and sE-selectin levels are higher in the anti-HCV-positive group of hemodialysis patients. [14,26,27] …”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that the sVCAM-1 level does not differ significantly between healthy volunteers and asymptomatic chronic hepatitis C carriers with minimal inflammatory grade. [26,28] The sVCAM-1 level increased only in the advanced fibrosis stage of HCV infection. Although patients with hemophilia A in this study did not exhibit symptoms of liver fibrosis, we nevertheless attempted to rule out the suspicion of chronic hepatitis C interference in sVCAM-1 levels.…”
Section: Discussionmentioning
confidence: 99%